(3QSGFd CHj ESMGb GdUGHFs - (3CHh ESMGb EHQGgje Hf gdGd Hf EHQGgje Hf RgQhf GdMQGfj GdUGHF,J (B384 (3g` s
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efgG(B: (3hdg Edi Cgd GdObg(B: (3GdOYjI CYRce Gddg MbjbI HGdGLeGY Ydi WdH GdSdGeI hSdhc ePgH GdGSJbGeI s
(3BNQgG (B:s
(3eHJhQI hCNQ GdehLhO ajgG(B: (3CeG HYO aEf CejQ GdeDejfdGjRGd eLJgOkG ai eUGdM GdeSdejf hHCYKGdge Ydi eQGTO GdOfjG hGdOjf , hegjHG Cdgeg Edi CMSf GdENJjGQ ajeG jhQOhf hjUOQhf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B124s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B16 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs